Design of a half‐ring type dipole antenna for WLAN communications. Issue 8 (August 2014) - Lee, Hyeonjin; Cheong, Seahansol; Kim, Young‐Chul
ABSTRACT In this article, a novel and compact printed half‐ring dipole antenna for WLAN communications is proposed. The proposed dipole antenna consists of a tapered balun and a pair of half‐ring dipole which have both the modified microstrip half‐ring with a feed line and the modified microstrip half‐ring with the tapered balun on the ground plane. The proposed antenna has a decreased physical size and radiates an omnidirectional pattern compared with conventional dipole antenna because of the proposed ring dipole antenna uses a circular‐type dipole. Prototypes of the proposed antenna for the 4.9–6 GHz bands are constructed and tested. The proposed antenna obtains a measured peak gain of about 5.8 dBi at 5.32 GHz, and an appeared circular polarization pattern at 5.04 GHz. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1832–1836, 2014